Three-piece add-on posterior chamber intraocular lens implantation for the correction of symptomatic pseudophakic ametropia: a retrospective study - Mahmoud F Rateb; Mohammed N El-Mohamady; Ibrahim M Ahmed (Wolters Kluwer Medknow Publications, 2018)
Purpose To evaluate the implantation of secondary low-power sulcus piggyback posterior chamber intraocular lenses (PCIOLs) for the correction of unaccepted postoperative refractive surprises or anisometropia. Patients and methods We retrospectively reviewed 17 cases with uncomplicated cataract extraction using phacoemulsification with in-the-bag PCIOL implantation and undesired residual postoperative refractive error. Patients underwent secondary piggyback intraocular lens implantation with add-on monofocal SECURA-sPB through a 3.2-mm clear corneal incision. The primary outcome measure was uncorrected distance visual acuity. Moreover, we evaluated intraoperative or postoperative complications. Results The mean age of patients was 65.2±10.1 years. The mean time to piggyback lens insertion was 6.5±3.1 months, and the mean follow-up period was 14.4±4.6 months. The mean preoperative uncorrected distance visual acuity was 20/80, and it increased significantly to be 20/30 postoperatively (P<0.001). The mean preoperative cylinder was 1.30±0.70 D, and it decreased significantly to be 0.54±0.45 postoperatively (P<0.001). The mean preoperative spherical deviation from emmetropia was 3.4±0.73 D, and the postoperative arithmetic prediction error mean was −0.32±0.55 D. No major intraoperative or postoperative complications were recorded. Conclusion Low-power add-on sulcus PCIOLs provided safe and effective refractive results in pseudophakic patients with refractive surprises.